HIF-1α Is Associated with Resistance to Hypoxia-Induced Apoptosis in Ameloblastoma - Katherine Julissa Palma Valladares; Karolyny Martins Balbinot; Antonia Taiane Lopes de Moraes; Maria Sueli da Silva Kataoka; Aline Maria Pereira Cruz Ramos; Rommel Thiago Jucá Ramos; Artur Luiz da Costa da Silva; Ricardo Alves Mesquita; David Normando; Sérgio de Melo Alves Júnior; João de Jesus Viana Pinheiro (International Journal of Dentistry)
Background. Ameloblastoma (AMB) is a benign odontogenic tumour, with an aggressive local behaviour and a high rate of recurrence. Previous studies have demonstrated that hypoxia-induced factor alpha 1 (HIF-1α) and activated caspase-3 contribute to tumour invasiveness and cytogenesis in ameloblastoma. Hypoxia increases HIF-1α levels, which triggers a number of signalling pathways. This paper aimed to present data in the study of hypoxia-activated signalling pathways that modulate proapoptotic and antiapoptotic events in AMB. Methods. Twenty cases of AMB and ten cases of dental follicle (DF) were used to analyse the immunoexpression of HIF-1α, p53, BNIP3, Bcl-2, IAP-2, GLUT1, and Bax. To contribute to the study, an analysis of expression and genetic interaction was performed using the cell line AME-1. Results. AMB and DF expressed the studied proteins. These proteins showed significantly greater immunoexpression in AMB compared with the DF (p<0.05). HIF-1α showed an important association with GLUT1, and a positive correlation was observed among p53, Bcl-2, and IAP-2. Transcriptomic analysis showed the significant expression of the studied proteins, and the network generated showed a direct association of HIF-1αF with GLUT1 (SLC2A1), TP53, and LDHA. Interestingly, GLUT1 also exhibited direct interaction with TP53 and LDHA. Conclusion. In AMB tumorigenesis, hypoxia is possibly related to antiapoptotic events, which suggests an important role for HIF-1α, GLUT1, Bcl-2, IAP-2, and possibly p53.